The MYH7 p.R787H mutation causes hypertrophic cardiomyopathy in two unrelated families - Purushotham, G (Pulsus Group Inc, 2010)
BACKGROUND: Familial hypertrophic cardiomyopathy (FHC) is a Mendelian disorder usually caused by mutations in any one of more than 12 genes, most of which encode sarcomere proteins. The disease exhibits extensive genetic heterogeneity, and it is important to identify mutations that result in adverse symptoms and/or lethality in affected individuals. An analysis of disease-causing mutations has been initiated in the Indian population to determine prevalent mutations. METHODS: FHC was detected using echocardiography and by analysis of clinical symptoms and family history. The disease-causing mutation was identified using polymerase chain reaction DNA sequencing. RESULTS: The p.R787H mutation was identified in the MYH7 gene in two FHC families. Sequence and structure analysis suggested impaired binding of the mutant protein to the myosin essential light chain. CONCLUSIONS: Although the mutation results in variable clinical symptoms in the affected individuals, probably owing to the effect of modifier genes and/or environmental factors, it does not appear to be a lethal mutation.